Anticoagulant-induced priapism progressing to penile gangrene: a devastating complication!. (21st November 2012) - Nagathan, Deepak Sharanappa; Pahwa, Harvinder Singh; Kumar, Awanish; Goel, Apul
Abstract : A 35-year-old man developed priapism with the use of low-molecular-weight heparin and warfarin following repair of left brachial artery sustained after gunshot injury. Priapism progressed to penile gangrene despite decompression and distal shunt procedure leading to total penectomy and perineal urethrostomy. We describe the mechanism of anticoagulant (heparin and warfarin)-induced penile gangrene and the possible methods to avert such a devastating complication.